(untitled) (Brazilian Journal of Radiation Sciences, 2022)
The IPR-R1 Triga research reactor, located at CDTN (Nuclear Technology Development Center) in Brazil, is one of the oldest reactors in operation worldwide. The Brazilian Nuclear Energy Commission (Cnen) has granted a Permit for Permanent Operation license for the CDTN Triga reactor. This authorization includes some conditions to be settled within a period of up to two years, that is, until the end of 2019, which has not yet been carried out and is currently being prepared by CDTN. For this purpose, Project 0006.23 – Maintenance of Licensing of the IPR-R1 Triga Reactor was created in CDTN’s Multiannual Program. In this project is included the Subproject: 6.23.3 – Preparation of the system to manage the aging of the IPR-R1 Triga reactor. Inserted in this context, the main objective of this paper is the proposal of good practices to be adopted in the future by CDTN, related to the Projects of Licensing and Aging of Triga reactor, for the management and physicochemical control of its cooling water, considering its electrical conductivity and pH, following IAEA recommendations. So, the present work is relevant, as it addresses a proposal for monitoring and controlling pH and electrical conductivity of the cooling water of Triga reactor. As a result of this proposal, the useful life of Triga reactor may be extended and there will be greater reliability and safety in its operation.